Penggunaan Multimedia Interaktif Berbasis Autoplay Media Studio Untuk Meningkatkan Hasil Belajar Fisika di Kelas XI SMA Negeri 8 Tikep Pada Konsep Fluida Statis - Marwiya Muksin; Nursanti Ali (Peneliti.net, 2022)
This Research Aims To Know The Use Of Interactive Multimedia Based On Autoplay Media Studio Against Student Learning Outcomes of Class XI SMA Negeri 8 Tikep on Fluid Concepts. The type of research used is experimental research with a pretest - posttest control group design . This research was carried out in class XI students of SMA Negeri 8 Tikep which totaled 47 students spread over 2 classes and the sample in this study were students of class XI IPA 1 (as an experimental class) and class IPA 2 (as a control class). Collecting data in this study is by using a test in the form of a description. The results obtained by the average student learning outcomes increased. The average post-test results using the use of interactive multimedia (MMI) Autoplay Media Studio Model drill and practice in the experimental class was 79.56 while using the powerpoint media lecture method in the control class the average value was 58.90. The results of the analysis of hypothesis testing using the independent test Sample T_test assisted by SPSS 21.0 obtained t_count of 3.742 > t_table value of 2.014 so that H_0 is rejected and H_1 is accepted which means there is an increase in learning outcomes using Interactive Multimedia based on Autoplay media studio drill and practice models